Approximate controllability of second-order distributed implicit functional systems - Henriquez, Hernan R; Hernandez, Eduardo (Nonlinear analysis, 2009)
In this paper we study the approximate controllability of control systems with states and controls in Hilbert spaces, and described by a second-order semilinear abstract functional differential equation with infinite delay. Initially we establish a characterization for the approximate controllability of a second-order abstract linear system and, in the last section, we compare the approximate controllability of a semilinear abstract functional system with the approximate controllability of the associated linear system.